Review article: Topical antibiotic treatments for acute otitis externa: Emergency care guidelines from an ear, nose and throat perspective. (26th September 2021) - Khatri, Hershil; Huang, Johnson; Guazzo, Emily; Bond, Craig
Abstract: Acute otitis externa (AOE), also known as 'swimmer's ear', is a common acute problem. It is one of the most common ED presentations. Atypical organisms, recalcitrant disease and antibiotic options contribute to making AOE a clinical challenge. There are a number of red flags associated with AOE which require consideration when treating patients with AOE. We discuss an evidence‐based approach to management of AOE in the emergency setting, with indications for specialist referral. Abstract : Acute otitis externa (AOE), also known as 'swimmer's ear', is a common ED presentation; atypical organisms, recalcitrant disease and antibiotic options contribute to making AOE a clinical challenge. There are a number of red flags associated with AOE which require consideration when treating patients with AOE. We discuss an evidence‐based approach to management of AOE in the emergency setting, with indications for specialist referral.